2004
DOI: 10.1038/nature02949
|View full text |Cite
|
Sign up to set email alerts
|

A socially enforced signal of quality in a paper wasp

Abstract: Organisms use signals of quality to communicate information about aspects of their relative phenotypic and genetic constitution. Badges of status are a subset of signals of quality that reveal information about an individual's size and dominance. In general, signals of quality require high and differential costs to remain honest (that is, prevent low-quality cheaters from exploiting any fitness benefits associated with communicating high quality). The theoretically required costs for badges of status remain co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
342
4
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 410 publications
(364 citation statements)
references
References 26 publications
15
342
4
3
Order By: Relevance
“…Under this hypothesis, experimentally altering a badge creates a mismatch between the manipulated patch and behavior (Järvi et al 1987) of the experimental bird which leads to conflicting signals about their dominance status. As a result, the receiver may increase aggression towards the signaler to "test" its dominance status and enforce signal honesty by social means (Rohwer, 1975(Rohwer, , 1982Tibbetts and Dale, 2004). The results of our experimental manipulation are consistent with both of the above hypotheses.…”
Section: Discussionsupporting
confidence: 79%
“…Under this hypothesis, experimentally altering a badge creates a mismatch between the manipulated patch and behavior (Järvi et al 1987) of the experimental bird which leads to conflicting signals about their dominance status. As a result, the receiver may increase aggression towards the signaler to "test" its dominance status and enforce signal honesty by social means (Rohwer, 1975(Rohwer, , 1982Tibbetts and Dale, 2004). The results of our experimental manipulation are consistent with both of the above hypotheses.…”
Section: Discussionsupporting
confidence: 79%
“…Low-volatility pheromones, including cuticular hydrocarbons, are perceived by the antennae and are important in paper wasp social recognition (Panek et al, 2000;Dapporto et al, 2004). Tibbetts and Dale (2004) recently demonstrated that Polistes females can respond to visual cues of social rank as well. A general increase in cognitive capacity, distributed among brain regions, may be necessary for dominant females.…”
Section: Discussionmentioning
confidence: 99%
“…However, because the person has conveyed information that does not accurately reflect the true state of affairs (remembering that by definition a suicide gesture is intended to give the false impression that one intends to die as a result of their behavior), this behavior often is met with negative reactions from others (cf. Tibbetts & Dale, 2004). In addition, suicide gestures also may elicit a negative response because they represent a lack of cooperation with the larger group.…”
Section: Animal Signalingmentioning
confidence: 99%